-7(3r-4)=-20+9r

Simple and best practice solution for -7(3r-4)=-20+9r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(3r-4)=-20+9r equation:


-7(3r-4)=-20+9r

We simplify the equation to the form, which is simple to understand
-7(3r-4)=-20+9r

Reorder the terms in parentheses
+(-21r+28)=-20+9r

Remove unnecessary parentheses
-21r+28=-20+9r

We move all terms containing r to the left and all other terms to the right.
-21r-9r=-20-28

We simplify left and right side of the equation.
-30r=-48

We divide both sides of the equation by -30 to get r.
r=1.6

See similar equations:

| 28-13.8x=-54.8 | | 4s-12*(s-2)=s | | 20z+3z-21z-1=13 | | -78=6U+12 | | 3x-3+x-3=90 | | (6x^3y^2)(-2x^2y)= | | -6+3(1-8k)=27 | | -22=2-3r+7r | | 5(3x-6)=10 | | -0.5s=-28 | | 198=g+12 | | 42=-2(v-8) | | 7+0=x | | -21=9d-7d | | 220=g+70 | | 5(c-6)c+11=24 | | -12=6(x+7) | | 7+y+12y=7 | | -8n+2=-3n-3 | | -5p-24=21(-1+3p) | | b+3-9=29 | | 4(-3+v)=36 | | f(5)=4x-3 | | -5(2s+2m)= | | -111=-3(1+6n) | | 50+5x=15+12x | | 12x-5=4x-1 | | 7x+11=7+7x | | -2(-4+y)-5y=15 | | -13+4b=-3b-7 | | 4x-3+2x+53=90 | | y=5x^2+2x-1 |

Equations solver categories